Cardiovascular diseases mortality in Brazilian municipalities: estimates from the Global Burden of Disease study, 2000–2018Research in context - Luisa Campos Caldeira Brant; Juliana Bottoni Souza; Bruno Ramos Nascimento; Beatriz Polachini Assunes Gonçalves; Ana Luiza Assumpção Ciminelli; Antonio Luiz Pinho Ribeiro; Deborah Carvalho Malta (The Lancet Regional Health. Americas)
Summary: Background: Age-standardized mortality rates (ASMR) for cardiovascular diseases (CVD) have decreased in Brazil in the last decades due to better control of risk factors and access to healthcare. However, how this reduction is distributed across the country's municipalities is unknown. We aimed to evaluate changes in CVD mortality rates across Brazilian municipalities from 2000 to 2018 using estimates from the Global Burden of Disease (GBD) study. Methods: In this ecological study, ASMR for CVD were estimated using GBD methodology for 5564 Brazilian municipalities from 5 regions in the triennials: 2000–2002, 2009–2011, 2016–2018. A visuospatial analysis was applied to create clusters in ASMR with Moran Local analysis. Municipalities were stratified by population size in <30,000, 30,000–300,000, and >300,000 inhabitants per region. The % changes in ASMR from 2000–2002 to 2016–2018 were calculated. Findings: In 2000–2002, ASMR for CVD were higher in more developed regions and in larger municipalities of all regions, except for the South. In 2016–2018, CVD ASMR increased in the least developed Northern regions. The % reduction in CVD ASMR was lower in small vs large municipalities within all 5 regions, varying from −3% in small Northern municipalities to −43% in large Southern municipalities. Interpretation: The reduction in CVD mortality in Brazil was lower in municipalities from the most vulnerable regions and smaller populations. Public policies tailored to these smaller municipalities, particularly on the least developed regions, must be considered a priority. Funding: Brazilian Ministry of Health [grant 148/2018] and Pan American Health Organization [Letter of Agreement SCON2021-00288].